Annual Equivalent Value, Benefit Cost Ratio, and Composite Performance Index as Valuation Appraisal Support of Teakwood Plantation - Sugiharto Soeleman; Endang Gumbira Sa'id; Heny Kuswanti Suwarsinah Daryanto; Arif Imam Suroso (Institut Pertanian Bogor (IPB University), 2014)
Teak (Tectona grandis L.f) is a premium high-value hardwood species being viewed as the most preferred species for investment opportunity. Recently, there has been a gradual move away from state control of teakwood plantation toward the participation of private enterprises. Several enterprises offer investment opportunity of teakwood plantation in which one of the main selling points being offered is a quick harvesting schedule. A quick harvesting time, however, might not provide the best outcome to the investors. This research exercise and compare the valuation appraisal of different harvesting schedules. The research focused on project planning, enterprise budget, financial projection, and valuation measurements to arrive at overall appraisal. To avoid any possible bias of individual investor's preference on common valuation criteria such as total investment, net cash flow (NCF), net present value (NPV), internal rate of return (IRR), profit on investment (P/I), and payback period (PBP), 3 otherS criteria namely benefit cost ratio (BCR), annual equivalent value (AEV), and composite performance index (CPI) have been applied to arrive at a more fair valuation. It is concluded that the longer the harvesting schedule, the better valuation outcome could be achieved, and therefore, investors should critically review any investment proposal in accordance to their preference on valuation criteria.